The assault - Mulisch, Harry, 1927- (New York : Pantheon Books, 1985)
In the last days of 1945 in Holland, an entire family is massacred except for one twelve-year-old son, and the repercussions of this nightmarish event follow him the rest of his life.
Translation of: De aanslag.
Adult
Keywords: Netherlands -- History -- German occupation, 1940-1945 -- Fiction; Netherlands -- History -- 1940-1945, German occupation -- Fiction